Immune-related Neutropenia Following Treatment With Immune Checkpoint Inhibitors. Issue 2 (February 2020) - Finkel, Inbar; Sternschuss, Michal; Wollner, Mira; Shamai, Sivan; Peled, Nir; Turgeman, Ilit; Shochat, Tzippy; Dudnik, Elizabeth
Abstract : The existing data with regard to immune-related neutropenia (irN), a rare (incidence—1%) immune-related adverse event of immune checkpoint inhibitors, are scarce. Eight patients with irN were identified through internal databases of 3 participating Israeli cancer centers. In addition, 11 original articles focusing on the clinical course of 24 patients with irN were selected during the PubMed search. Descriptive analysis of clinical and pathologic factors related to irN was performed (n=32); the effect of these on the irN outcomes was assessed. An algorithm for irN evaluation and treatment was proposed. The median time-to-onset of irN (n=32) was 60 days (range, 10–465 d). Grade 3–5 irN, febrile neutropenia, and irN-related death occurred in 81%, 50%, and 9% of patients, respectively. In all, 56%, 22%, 62%, and 25% of patients received PO corticosteroids, IV corticosteroids, granulocyte colony–stimulating factor (GCSF), and intravenous immunoglobulins (IVIG), respectively, with an improvement/resolution rate of 84%. Odds ratios for irN improvement/resolution were as follows: 1.40 [95% confidence interval (CI), 0.03–68.72], 0.43 (95% CI, 0.04–4.22), 2.60 (95% CI, 0.07–97.24), 0.36 (95% CI, 0.03–4.38), 4.02 (95% CI, 0.16–99.48), 2.01 (95% CI, 0.32–12.70), 1.08 (95% CI, 0.02–49.89), 0.42 (95% CI, 0.06–2.91), and 2.73 (95% CI, 0.42–17.51) for granulocyte hyperplasia, granulocyte/all lineage hypoplasia, granulocyte maturation blockade, lymphocyte infiltration on bone marrow biopsy, IV corticosteroids, PO corticosteroids, cyclosporine, IVIG, and GCSF, respectively ( P >0.05 for all factors). IrN recurrence rate following immune checkpoint inhibitors rechallenge was 80%. IrN is a rare, life-threatening, early-onset immune-related adverse event. Differentiating between the central, peripheral, and modified peripheral types allows a better prognosis definition. Corticosteroids and GCSF represent the main treatment approaches; IVIG and cyclosporine should be used as salvage treatment.